BH3 ⋅ Me2S: An Alternative Hydride Source for NiH‐Catalyzed Reductive Migratory Hydroarylation and Hydroalkenylation of Alkenes. Issue 10 (26th February 2021) - Liu, Jiandong; Gong, Hegui; Zhu, Shaolin
Abstract: Borane dimethylsulfide (BMS) was found to be an efficient hydride source for nickel‐hydride catalyzed reductive migratory hydrofunctionalization reactions. Catalytic reductive migratory hydroarylation and migratory hydroalkenylation were achieved with BMS in high yields and with excellent regioselectivity. A large‐scale experiment employing as little as 0.5 equivalents of BH3 ⋅ Me2 S as the hydride source delivered the desired migratory hydroarylation product in high yield and selectivity. Abstract : The inexpensive borane dimethylsulfide (BMS) complex was found to be an efficient hydride source for nickel‐hydride catalyzed migratory hydrofunctionalization. Using BMS, migratory hydroarylation and migratory hydroalkenylation were achieved with broad substrate scope under mild conditions.